Construction of novel probes and their applications in resistant bacteria - Aw, Junxin (2018)
The rapid spread of antibiotics resistant bacteria has raised a huge threat to our human community. The development of new techniques for the real-time visualization of such pathogenic bacteria and its biochemical changes in a human body system has become critically important. Through the rapid advancement of optical imaging technology, it has enabled us to have a non-invasive and real time monitoring for this wide spread of antibiotic resistant bacteria. One of main methods bacteria express resistance is the secretion of Beta lactamase (Bla) enzyme, which can be hydrolyzed by 4-membered beta-lactam ring in antibiotics such as penicillin leading to therapeutic failure. Therefore, it becomes increasingly important to construct novel optical imaging probes that are capable to specifically detect such resistant enzymes in living system. In this dissertation, we have synthesized and constructed some smart molecular probes to further advance their biological applications in vitro and in vivo, as shown in the following parts. In chapter 2, a selective enzyme responsive molecule 1 termed as ERM-1 is designed and constructed to localize on the surface of pathogenic bacteria for bioimaging of the biofilm formation, which expresses AmpC, one typical class C type of beta-lactamase. In this study, we have chosen tetraphenylethylene (TPE) moiety as our target fluorophore, which was covalently conjugated to the cephalosporin molecule. One of the key reasons we used TPE is due to its promising aggregation induced emission (AlE) property at 478 nm. The aggregated TPE products after enzyme interactions could potentially overcome the common issues related with random diffusion and thus can serve as a reliable probe to real-time image biofilms with different bacterial pathogens. In chapter 3, an enzyme responsive cephalosporin molecule conjugated lanthanide upconversion nanoparticles (UCNs) have been developed which can be used to realtime monitor antibiotic resistant pathogenic bacteria at higher wavelength with lower photo-damage and better tissue penetration. Typically, in the presence ofBla enzyme in living cells, the cephalosporin's conjugate on UCNs will be hydrolyzed at its 4- membered beta lactam ring by the serine-70 functional group by penicillin binding protein (PBP), which leads to the expulsion of the quencher Dabcyl. Thus, the FRET between FITC and Dabcyl is disrupted and enzyme activity will be detected. This specific nanoplatform can be utilized to detect P-lactamase as reporter gene and present promising imaging ability to monitor this drug resistant strains enzyme in living cells. In chapter 4, a new study based on bacterial surface amino acid metabolism pathway has been carried out which can efficiently localize and image the enzyme substrates on bacterial pathogens for specific bacterial resistance in vitro and in vivo. Basically, N3- contained amino acids will be involved in bacterial surface on the basis of essential metabolism pathways. Then the DBCO-contacting alkyne (C=C) modified betalactamase substrates will be covalently trapped on the bacterial surface through copperfree click chemistry. Such covalent linkage probe indicated promising activity to selectively recognize AmpC enzyme, in vitro and in vivo. In the last chapter, a study based on an enzyme responsive probe conjugated with lipid, which can very effectively localize on the surface of the bacteria, has been developed. In this study, the cephalosporin's probe conjugated on the lipid surface could be efficiently confined and localized in the lipid compartments of the bacteria membrane, thereby increasing the effective probe-enzyme interactions. Such unique probes indicated promising advantages compared to metabolic uptake and offers an attractive approach for labeling resistant bacteria without the need of artificial metabolic uptake or genetic engineering that may potentially perturb the endogenous properties of the bacteria.